(untitled) (Research, Society and Development, 2022)
Objective: to analyze the epidemiological profile of neonatal mortality from congenital syphilis in the Northeast region between 2016 and 2020. Methodology: This is an epidemiological, retrospective, descriptive study characteristic of neonatal deaths from syphilis designated in the Northeast between 206 2020, data were extracted through SIM and S1INASCs in DATASUS. The available information was informed with the scientific literature on the subject. Results: 253 neonatal deaths from congenital syphilis were reported in the place and period studied. The state of Pernambuco had a higher neonatal mortality ratio when compared to other states in the Northeast region. There was a greater number of cases in the male population and with regard to race/color there was a predominance of brown people, with a percentage of 72.72%. The vast majority of mothers had low or no education, with gestation duration between 32 and 36 weeks in deaths of children younger than 28 days due to SC. Conclusion: it is essential to provide health care with equity and the formulation of actions that promote the improvement of care provided to newborns with CS, thus reducing mortality rates.